MARX’S MATERIALISM IN THE MOVIE ENTITLED HUNGER GAMES TRILOGY - Auliana Dania Zulfa; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2024)
The Hunger Games is a trilogy of novels that were made into movies. The Hunger Games are related to social life, such as class conflict and materialism, this is interesting to examine in literary criticism using a Marxist approach. The topic of this research is Marx's materialism in the movies entitled Hunger Games trilogy. This research analyzes materialism related to class conflict, there are two class conflicts, namely, the bourgeoisie and the proletariat. This research focuses on two problems, namely, (1) the depiction of the bourgeoisie and proletariat in the movie Hunger Games sequel and (2) the effect of being bourgeoisie and proletariat toward the main characters. This research uses the theory of Marx (1998). This research uses descriptive qualitative methods. The results found a depiction of the bourgeoisie as powerful, wealth, and leadership. Meanwhile, the proletariat is a laborer or worker, poor, and powerless. This research finds the effects of being a bourgeoisie, namely, being powerful and oppressor while the proletariat becomes obedient and oppressed. Therefore, the aim of this research is that readers can learn about Marxism, especially about materialism related to class conflict namely, the bourgeoisie and the proletariat.